Estudo preditivo do impacto orçamentário da emenda constitucional nº 95/2016 nas universidades federais brasileiras - Oliveira, José Claudio Karam de (2018)
In any country, the theme of education is of high relevance, since education alone is capable of transforming society. Brazil has experienced increased access to free higher education in the last decade, with the creation of federal universities, as well as due to the greater availability of courses and number of vacancies in undergraduate programs underway. Following the economic and financial crisis that broke out in 2014 in Brazil, the National Congress approved the Constitutional Amendment No. 95/2016 (EC 95/2016), known as the Law of Public Expenditure Cap, to limit the growth of primary expenses, establishing another tax regime within the Fiscal Budget and Social Security of the Government for the next 20 years. In this context, the primary objective of this study is to analyze the budgetary impact of EC 95/2016 on the Brazilian federal universities over the next five years (2018-2022). Considering the scarce literature about the problem situation, this is an exploratory, quantitative study using econometric models with panel data to carry out a predictive study. The census sample of the study gathered the 63 Brazilian federal universities. Among the techniques used, documentary research main sources were the applicable legislation and the reports of the liquidated and paid expenses, whereas bibliographical research primary sources were authors that address the central theme of this paper, namely Public Budget and Public Accounting. The study broke down expenditure into three groups: (i) staff costs and charges, (ii) other current expenses, and (iii) investment and financial investment expenditures, projecting these expenditures into three different realities of the structure of these groups in view of the varying degrees of rigidity and contingency possibilities, to which all these groups of expenditure are subject. These situations were analyzed according to optimistic, neutral and pessimistic estimates, within the 95% confidence interval. The budgetary impact of imposing a cap on expenditure in the three circumstances and the three situations confirmed that Brazilian federal universities would no longer be able to adapt to the new fiscal regime, as early as of the first year in 2018. The predictive study revealed that the linear application of the expenditure cap implemented by EC 95/2016 on the budget of the federal universities would make their operations impracticable in the short term. The structural analysis of expenditure shows that investment spending is likely to be the most affected. If this forecast is not to be confirmed, the premise of nonredistribution of expenditure may be violated. In other words, to avoid the scrapping of higher education institutions, resources from other areas would have to be channeled to Higher Education. However, this is an eminently political decision, something about which one does not have objective parameters to make any statement.